2014
DOI: 10.1002/2013gl058684
|View full text |Cite
|
Sign up to set email alerts
|

A computationally efficient description of heterogeneous freezing: A simplified version of the Soccer ball model

Abstract: In a recent study, the Soccer ball model (SBM) was introduced for modeling and/or parameterizing heterogeneous ice nucleation processes. The model applies classical nucleation theory. It allows for a consistent description of both apparently singular and stochastic ice nucleation behavior, by distributing contact angles over the nucleation sites of a particle population assuming a Gaussian probability density function. The original SBM utilizes the Monte Carlo technique, which hampers its usage in atmospheric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 35 publications
4
65
0
Order By: Relevance
“…At warmer temperatures, between −10 • and −15 • C, there are no CFDC observation data to constrain the parameterizations because CFDC can not provide observation data at warm temperatures (> −15 • C). However, Niemand et al (2012) reported the Aerosol Interactions and Dynamics in the Atmosphere (AIDA) cloud chamber measurement of natural dust at temperatures of −13 and −16 • C with active fractions of 10 −4 and 10 −5 , which agree with our fitted active fractions from the α-PDF model. Saharan natural dust is reported in recent CFDC observations to have onset temperatures ranging from about −10 to −15 • C, which is consistent with laboratory observations of various types of surrogate dust (Phillips et al, 2012).…”
Section: Fitting Parameters For Natural Dust and Sootsupporting
confidence: 82%
See 2 more Smart Citations
“…At warmer temperatures, between −10 • and −15 • C, there are no CFDC observation data to constrain the parameterizations because CFDC can not provide observation data at warm temperatures (> −15 • C). However, Niemand et al (2012) reported the Aerosol Interactions and Dynamics in the Atmosphere (AIDA) cloud chamber measurement of natural dust at temperatures of −13 and −16 • C with active fractions of 10 −4 and 10 −5 , which agree with our fitted active fractions from the α-PDF model. Saharan natural dust is reported in recent CFDC observations to have onset temperatures ranging from about −10 to −15 • C, which is consistent with laboratory observations of various types of surrogate dust (Phillips et al, 2012).…”
Section: Fitting Parameters For Natural Dust and Sootsupporting
confidence: 82%
“…For example, for σ = 0.01, droplets freeze within a narrow temperature interval of about 10 • C, while for σ = 0.08, freezing occurs over a temperature range of about 18 • C. The change in the active fraction with temperature ( Fig. 10b) becomes smoother with an increase in the standard deviation, which indicates the "recovery" of singular behavior (Niedermeier et al, 2011(Niedermeier et al, , 2014Welti et al, 2012) and a weakening of the time dependence of stochastic behavior (see Fig. 2 for the change in time dependence with an increase in the standard deviation).…”
Section: Occurrence Frequency Of Ice Nucleation Modesmentioning
confidence: 97%
See 1 more Smart Citation
“…Specifically, a contact angle distribution was fitted to the LACIS measurements and was used, together with the soccer ball model (SBM; Niedermeier et al, 2011Niedermeier et al, , 2014, to simulate frozen fractions for different residence times varying over 4 orders of magnitude (i.e., 1, 10, 100 and 1000 s residence time). These frozen fractions were then used to calculate n s , shown as lines in Fig.…”
Section: Stochastic Nature Of Freezing and Time Dependencementioning
confidence: 99%
“…Time dependence arises from CNT because it is expressed as the rate of nucleation per unit time. Examples of this approach are Khvorostyanov and Curry (2000), Diehl and Wurzler (2004), Hoose (2010), Knopf (2011), Yang et al (2013), Wang et al (2014), andNiedermeier et al (2014).…”
Section: G Vali and J R Snider: Tdfr Parcel Modelmentioning
confidence: 99%